The uroradiology in diagnosis of tumors of the upper abdomen - Mendy Noriega, Fabián (Cirugía del Uruguay, 1971)
he thoracoabdominal regions, flanks and lumbar fossae, constitute a sector of the abdominal cavity where multiple viscera are grouped, some intra and others retroperitoneal, that are frequent seat of tumors of varied nature.